Comparison of Color Efficiency and Sensitivity Between Hydrogen Peroxide and Carbamide Peroxide: Literature review (Research, Society and Development, 2021)
Nowadays there are several methods of applying carbamide and hydrogen peroxide for use in dental whitening, this literature investigation tried to determine which is the best option. Objective: To compare through a literature review the efficacy of tooth color and sensitivity produced by hydrogen peroxide and carbamide peroxide. Method: The databases used were PUBMED, Scopus and Web of Science. The search method was “TOOTH WHITENING AND HYDROGEN PEROXIDE AND CARBAMIDE PEROXIDE”, applying the inclusion and exclusion criteria, 9 articles were obtained for this literature review. Result: According to the analyzed studies, it was found that all lightening agents improve the color appearance of dental structures. In most studies tooth sensitivity was present; however, carbamide peroxide produces less sensitivity.Conclusion: Hydrogen peroxide like carbamide peroxide are effective in producing a discoloration of teeth. In darker teeth the treatment is more effective regardless of the lightening agent used. On the other hand, the sensitivity is lower when carbamide peroxide is applied.